The failure of the spectacle: the voices within - Rothe, Dawn (Critical criminology, 2016)
This article offers an ethnobiographic analysis of one of the most marginalized populations in contemporary US society: impoverished individuals with schizophrenia, schizoaffective or mania hallucinatory bipolar disorder who are imprisoned, first within their minds, and secondly by the state, what I term "the spectacle." Punishment for their disease, rather than treatment, forces many of them into constant drift-transition between shelters, seedy motels and the streets: the spectacle’s disposable trash. I argue that to be recognized as a rights-worthy human being within the neoliberal spectacle individuals are required to have the financial, social and cultural resources necessary to actively participate in the labor market and the profit-generating activities of consumption and consumerism. The limited economic resources of the mentally ill keep them from being sufficiently active participants to be viewed as socially worthy. Consequently, they become socially unworthy—the socially dead. The seriously mentally ill experience both spatial and moral dislocation. They are cast out as flawed consumers and failed workers, and more importantly, due to the stigmatization of mental illness, they are disavowed of their humanity, rendering them socially dead.